2003
DOI: 10.1038/sj.pcan.4500587
|View full text |Cite
|
Sign up to set email alerts
|

High-grade intra-epithelial neoplasia and prostate cancer in Dibombari, Cameroon

Abstract: High-grade prostatic intra-epithelial neoplasia (HGPIN) occurs a decade earlier in men of African descent in the US and Brazil, compared to white men. Prostate cancer incidence and mortality is worse in the African-American than in US white men. Sub-Saharan Africa was thought to be a low incidence area. This disparity has been attributed to lifestyle factors such as diet. We report the results of prostatic biopsies, from an ongoing national prostate cancer survey. One hundred and eleven men aged 40 y and over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
9
2
Order By: Relevance
“…This study revealed a prevalence of prostate cancer of 10.4%, which support the hypothesis that there is a relatively high prevalence of prostate cancer in Bamenda, North West Region of Cameroon. This prevalence was similar to the prevalence of a research conducted in Ghana in 2015 with a prevalence of 9.4% [15][16][17][18][19][20][21] and that conducted in Dibombari, Cameroon with a prevalence of 8.0% [22]. However, this study revealed a relatively high prevalence of prostate cancer as opposed to previous research work conducted in Ghana with a prevalence of 7.0% [23] which could be as a result of difference in the methodology used.…”
Section: Discussionsupporting
confidence: 61%
“…This study revealed a prevalence of prostate cancer of 10.4%, which support the hypothesis that there is a relatively high prevalence of prostate cancer in Bamenda, North West Region of Cameroon. This prevalence was similar to the prevalence of a research conducted in Ghana in 2015 with a prevalence of 9.4% [15][16][17][18][19][20][21] and that conducted in Dibombari, Cameroon with a prevalence of 8.0% [22]. However, this study revealed a relatively high prevalence of prostate cancer as opposed to previous research work conducted in Ghana with a prevalence of 7.0% [23] which could be as a result of difference in the methodology used.…”
Section: Discussionsupporting
confidence: 61%
“…21,[35][36][37] African-American men also have the highest incidence of prostate cancer (about 50% more than Caucasians). 21,35,36,38,39 In contrast, Japanese men living in Osaka, Japan, have a significantly lower incidence of high-grade PIN compared to men residing in the United States, and Asians have the lowest clinically detected rate of prostate cancer. 40,41 Interestingly, Japanese men diagnosed with high-grade PIN also had an increased likelihood of developing prostate cancer, suggesting that high-grade PIN is a precursor of clinical prostate cancer in Asian men too.…”
Section: Epidemiology Of Pinmentioning
confidence: 99%
“…21,[35][36][37] African-American men also have the highest incidence of prostate cancer (about 50% more than Caucasians). 21,35,36,38,39 In contrast, Japanese men living in Osaka, Japan, have a significantly lower incidence of high-grade PIN compared to men residing in the United States, and Asians have the lowest clinically detected rate of prostate cancer. 40,41 Interestingly, Japanese men diagnosed with high-grade PIN also had an increased likelihood of developing prostate cancer, suggesting that high-grade PIN is a precursor of clinical prostate cancer in Asian men too.…”
Section: Epidemiology Of Pinmentioning
confidence: 99%